2008
DOI: 10.1002/j.0022-0337.2008.72.10.tb04595.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Assessment of Dental Hygiene Clinical Teaching Workshops

Abstract: Faculty development courses related to acquiring clinical teaching skills in the health professions are limited. Consequently, the Department of Dental Hygiene at the University of Texas Health Science Center at San Antonio conducted a series of clinical teaching workshops to address clinical teaching methodology. The goal of these workshops was to promote a problemsolving learning atmosphere for dental hygiene faculty to acquire and share sound clinical teaching strategies. To determine the value of the annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Educator’s responses strongly supported the use of a LMS such as WebCT especially in regard to the accessibility of the system, whilst at home. The valuing of discussion forums and groups sign‐up lists by educators indicates an alignment to socioconstructivist approaches to education where interaction among students becomes an instrument for collaborative learning and meaningful construction of knowledge 22 . The support for external weblink affordance is also significant.…”
Section: Discussionmentioning
confidence: 99%
“…Educator’s responses strongly supported the use of a LMS such as WebCT especially in regard to the accessibility of the system, whilst at home. The valuing of discussion forums and groups sign‐up lists by educators indicates an alignment to socioconstructivist approaches to education where interaction among students becomes an instrument for collaborative learning and meaningful construction of knowledge 22 . The support for external weblink affordance is also significant.…”
Section: Discussionmentioning
confidence: 99%
“…Many students report that discussions about treatment with row instructors (the dentists assigned to supervise the students in the clinic) in front of the patient can be intimidating. Other studies have found that ‘the establishment of a non‐threatening environment and respectful attitude encourages students to risk failure’, which is a critical element in clinical learning . Other identified strengths included mentors bringing much experience to guide them (63%), making students more comfortable in achieving their clinical competencies (64%) and being a good role model for the student (76%) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…These articles took readers through each stage of the PBL development process from introduction to key skills to an experiential exercise to facilitating group learning to assessment. In other examples, Hinton et al 22 described faculty development programs to create a culture for evidence‐based dentistry at Baylor College of Dentistry; Wallace and Infante 23 reported on workshops in clinical teaching skills they held at the University of Texas Health Science Center at San Antonio for faculty members in thirty‐eight dental hygiene programs; and Pyle and Goldberg 24 chronicled the steps taken by the faculty and administration to vision, plan, and implement transformational curricular change at Case School of Dental Medicine.…”
Section: Continuity and Change In Faculty‐related Researchmentioning
confidence: 99%